Antique Influences on Palekh Lacquered Miniatures - Lavrov, Dmitrii E. (Actual Problems of Theory and History of Art, 2015)
The article investigates antique themes and borrowings in regard to Palekh lacquered miniatures of the Soviet and modern Russian periods. The article justifies the actuality of such an investigation, due to both frequency of such appeals to antiquity by Palekh masters and the complete lack of researches in domestic and foreign literature. The author concludes that in the Soviet period antique borrowings were in the nature of “creative revival” of antiquity limited to certain forms, without simply copying those solutions, which had already been found. On the contrary, with the development of market relations in the Palekh lacquer craft, borrowings of ancient themes and images ceased to have any creativity, but became simple copies, often depicting antique themes from the academic pictures of the 19th century.
Keywords: Palekh miniature; antiquity; creative borrowing; copying; market relations